Diverse roles of heterogeneous nuclear ribonucleoproteins in viral life cycle - Bhattarai, Krishna; Holcik, Martin (Frontiers in Virology, 2022)
Understanding the host-virus interactions helps to decipher the viral replication strategies and pathogenesis. Viruses have limited genetic content and rely significantly on their host cell to establish a successful infection. Viruses depend on the host for a broad spectrum of cellular RNA-binding proteins (RBPs) throughout their life cycle. One of the major RBP families is the heterogeneous nuclear ribonucleoproteins (hnRNPs) family. hnRNPs are typically localized in the nucleus, where they form complexes with pre-mRNAs and contribute to many aspects of nucleic acid metabolism. hnRNPs contain RNA binding motifs and frequently function as RNA chaperones involved in pre-mRNA processing, RNA splicing, and export. Many hnRNPs shuttle between the nucleus and the cytoplasm and influence cytoplasmic processes such as mRNA stability, localization, and translation. The interactions between the hnRNPs and viral components are well-known. They are critical for processing viral nucleic acids and proteins and, therefore, impact the success of the viral infection. This review discusses the molecular mechanisms by which hnRNPs interact with and regulate each stage of the viral life cycle, such as replication, splicing, translation, and assembly of virus progeny. In addition, we expand on the role of hnRNPs in the antiviral response and as potential targets for antiviral drug research and development.